Video Kartun dan Video Animasi dapat Menurunkan Tingkat Kecemasan Pre Operasi pada Anak Usia Pra Sekolah - Ajeng Dwi Retnani; Titin Sutini; Suhendar Sulaeman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to analyze the effect of cartoon videos and animated videos on reducing preoperative anxiety levels in pre-school age children. This research method uses quasi-experimental with a pre and post-test approach with out control. The results showed that the reduction in preoperative anxiety levels in pre-school children after being given a cartoon video intervention by 4.20, after being given an animated video intervention by 4.70 and after being given a combination intervention between cartoon videos + animated videos by 7.20. Based on this, the level of preoperative anxiety using a cartoon video + animated video combination intervention showed the greatest decrease. The results of the study also obtained p value> 0,000. Conclusions, the influence of cartoon videos and animated videos on the reduction of preoperative anxiety levels in pre-school age children. Keywords: Animation, Anxiety, Pre Operation, Cartoon Video